(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2021)
The aim of this paper is to present the teaching of addition and subtraction in early-childhood education as a two-way process. According to this idea, we have designed, developed and evaluated a didactic proposal with two types of activities: on the one hand, the resolution of arithmetic problems of addition and subtraction framed in “The three little pigs” tale; on the other hand, the resolution of basic calculations. To do this, we have analyzed the different types of arithmetic problems that four-year-old students are able to solve and the strategies they usually use to do it. We have also considered the curriculum; the textbook students use in their lessons and the teacher’s opinion to characterize the current teaching of the addition and the subtraction.